Making performance management relevant in complex and inter-institutional contexts: using outcomes as performance attractors. Issue 3 (17th February 2021) - French, Max; Mollinger-Sahba, Ali
Abstract : Purpose: Modern public service systems tackle many complex issues by operating across institutional boundaries. Performance management must operate in this context without clear lines of accountability or central authority. This paper introduces and develops the theoretical mechanism of "performance attraction" to describe how outcomes and associated performance indicators can operate as organising instruments in inter-institutional contexts by attracting, rather than directing, institutional behaviour. Design/methodology/approach: We explore the "performance attractor" role played by outcomes through a multiple case study analysis of three prominent outcomes frameworks operating at the regional, national and international levels: the Scottish Government's National Performance Framework, the Western Australian Alliance to End Homelessness Outcomes Measurement and Evaluation Framework and the United Nations' Sustainable Development Goals. Findings: We find support for two theorised mechanisms facilitated by the performance attractor concept: (1) that performance attractors enable coordination by creating a shared sense of responsibility for interdependent goals while also permitting autonomous navigation of individual contexts and (2) that performance attractors support performance improvement by motivating collective learning and adaptation informed by institutional interdependencies. Cases relied primarily on voluntary adoption of outcomes frameworks, rather than utilising more coercive forms of accountability. Further studies should explore the institutional response to performance attractors to better understand the potential of this mechanism. Originality/value: The paper contributes to a growing body of critical literature that has explored alternatives to traditional control-oriented performance management in complex and inter-institutional settings. We describe design principles that policymakers and practitioners can adopt to construct more effective performance frameworks in these conditions.